2011
DOI: 10.1007/s11430-010-4163-0
|View full text |Cite
|
Sign up to set email alerts
|

Mantle dynamics of the reactivating North China Craton: Constraints from the topographies of the 410-km and 660-km discontinuities

Abstract: The topographies of the 410-km and 660-km discontinuities have important implications for mantle dynamics. Here we present high-resolution seismic imaging of the 410-km and 660-km discontinuities beneath the North China Craton (NCC) employing the receiver function method. Depth anomalies (deeper or shallower than the global average depths) at both discontinuities were detected by introducing a three-dimensional regional velocity model. The depressions of the 410-km discontinuity are mostly located in the easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…Since Pliocene or earlier, the inherited regional tectonic stress characteristics led to the formation of an NW-SE stretching stress environment (Zhang et al 2003;Zhu et al 2013). The deep substances migrated eastward owing to the control of the long-range effect of the Indian Plate, while the upper-mantle substances upwelled owing to the blocking effect (subduction) of the Pacific-Philippine Plate (Xu et al 2011). The North China basin depression as well as the normal fractures of its major faults was formed under this background (Jia et al 2014).…”
Section: Theoretical Analysismentioning
confidence: 95%
“…Since Pliocene or earlier, the inherited regional tectonic stress characteristics led to the formation of an NW-SE stretching stress environment (Zhang et al 2003;Zhu et al 2013). The deep substances migrated eastward owing to the control of the long-range effect of the Indian Plate, while the upper-mantle substances upwelled owing to the blocking effect (subduction) of the Pacific-Philippine Plate (Xu et al 2011). The North China basin depression as well as the normal fractures of its major faults was formed under this background (Jia et al 2014).…”
Section: Theoretical Analysismentioning
confidence: 95%
“…It has long been realized that the structure of major discontinuities in the Earth's deep interior is of key importance in the context of plate tectonics and mantle dynamics, and therefore is pivotal to unraveling the deep processes and mechanisms of cratonic destruction. Based on the dense seismic array data, the discontinuity structure of the mantle transition zone beneath the NCC has been carefully investigated and imaged [42][43][44][45]. The imaging results show that the thickness of the mantle transition zone varies sharply at around the boundary between the eastern and central NCC, which coincides with an obvious variation in the structural features of the lower boundary of the mantle transition zone (the 660-km discontinuity) (Figure 3(a)).…”
Section: Deep Dynamics Of the Ncc Destructionmentioning
confidence: 99%
“…The newly constructed seismic images reveal a close correspondence between the geographic scope of lithospheric modification and destruction and the surface geological structures as well as the morphology of the stagnant Pacific slab in the mantle transition zone beneath the NCC (Figures 2 and 3). The striking structural features suggest that the subduction process of the Pacific Plate has strongly affected the entire upper mantle and the overlying lithosphere system of the eastern NCC in a coupled manner [45]. The Pacific subduction may have caused unsteady mantle flow, which resulted in a highly heterogeneous discontinuity structure of the mantle transition zone; the continuous subduction probably also led to partial penetration of the stagnant slab into the lower mantle, decompression melting and upward migration of hot mantle materials.…”
Section: Mechanism Of the Ncc Destructionmentioning
confidence: 99%
“…Many studies have shown that there are regional variations of rock compositions and velocity structure in the crust and the upper mantle in the North China Craton (Gao et al 2010;Xu et al 2011). At present, there are two controversial hypotheses about what leads to the destruction in the NCC: one is plate edge effect caused by plate movement (Gao et al 2002;Wu et al 2005), and the other is driven primarily by plate basal force associated with smallscale mantle convection (Xu 2001).…”
Section: Introductionmentioning
confidence: 99%